Konsep Pembelajaran PAI bagi Anak Berkebutuhan Khusus di Sekolah Inklusi: Studi Kasus di SD Semai Jepara - Ana Rahmawati (Faculty of Education and Teacher Training, Institut Agama Islam Negeri Pekalongan, 2018)
Education plays a very pivotal role for human beings in achieving social welfare, without any discrimination, including children with special needs. The existence of inclusive schools becomes a solution in fulfilling special needs children’s right to education. It is due to the fact that they can learn and socialize with physically and mentally healthy children in inclusive schools. This present study aims to explore the learning concept of Islamic education applied for teaching children with special needs at SD Semai Jepara, one of inclusive schools in Central Java-Indonesia. A qualitative descriptive approach was designed in this research. The findings promote that the implementation of Islamic education at SD Semai Jepara was similar to the one in regular schools. It indicates that the materials taught to the students were just the same. Nonetheless, the teaching methods used in delivering the materials were different. One of the teaching methods employed in teaching Islamic education for the special needs children was parody. Additionally, in certain materials, the children were divided into two learning groups, namely: large and small ones, to enhance the teaching and learning processes. This study also exposes that the teachers are supposed to be as creative as possible in creating appropriate learning atmosphere in teaching Islamic education since there are lots of students with the variety of backgrounds who possess special needs.